Early Pleistocene hominin teeth from Meipu, southern China. Issue 151 (February 2021) - Xing, Song; Martinón-Torres, María; Deng, Chenglong; Shao, Qingfeng; Wang, Yuan; Luo, Yunbing; Zhou, Xingming; Pan, Lei; Ge, Junyi; Bermúdez de Castro, José María; Liu, Wu
Abstract: The rarity and poor preservation of hominin fossils from the East Asian Early Pleistocene hamper our understanding of their taxonomy and possible phylogenetic relationship with other members of the genus Homo . In the 1970s, four isolated hominin teeth were recovered from the Meipu site, southern China, which biostratigraphic analysis placed in the late Early Pleistocene. Early reports assigned the teeth to late Homo erectus . Since then, the teeth have not been re-evaluated, nor has reliable dating been performed at the Meipu site. Here, biostratigraphic and paleomagnetic dating allow for a more precise chronological constraint of the Meipu hominins in the late Early Pleistocene, between 780 ka and 990 ka, making them one of the few known hominins for this time in mainland Asia. The comparison of the morphology of the Meipu teeth with other members of the genus Homo reveals that the Meipu teeth preserve traits such as moderate shoveling of the I 1, the square crown contour of M 1, and a buccolingually wider lingual cusp in P 4 that make them closer to early Homo specimens from Africa and Homo ergaster from Dmanisi (Georgia). In addition, the Meipu teeth exhibit features that are more typical for late mainland East Asian H. erectus, such as the moderately convex I 1 labial surface and a pronouncedly convex I2 labial surface. In these features, the Meipu hominins are morphologically intermediate between African/Dmanisi early Homo and East Asian Middle Pleistocene hominins. This study contributes to a better understanding of the morphologies and the taxonomic status of East Asian Early Pleistocene hominins, a time period for which the hominin evidence with secure stratigraphic context is scarce.